GAMBARAN KOMPLIKASI DAN TEMUAN INTRAOPERASI PADA PASIEN OTITIS MEDIA SUPURATIF KRONIK DENGAN KOLESTEATOMA DI RUMAH SAKIT HAJI MINA MEDAN TAHUN 2015 SAMPAI 2019 - SIUL HIDAYATI; MUHAMMAD EDY SYAHPUTRA NASUTION (LP2MTBM MAKARIOZ, 2021)
Chronic suppurative otitis media (CSOM) with cholesteatoma is a disease with high morbidity and mortality due to itscomplications. Cholesteatoma can cause bone erosion and damage to surrounding structures resulting in seriouscomplications. This study aims to determine the complications and intraoperative findings that can be found in CSOMpatients with cholesteatoma at RS Haji Mina Medan in 2015-2019. This study is descriptive in nature with 50 medical recordsof CSOM patients with cholesteatoma in 2015-2019. This research was conducted from June 2020-January 2021 at theT.H.T.K.L Department and the medical records department at the Medan Hajj Hospital. Univariate analysis was performedon each research variable and the category of frequency distribution of each variable was expressed as a percentage. It wasfound that the age range of CSOM sufferers with the most cholesteatoma was 21-30 years (48%). More CSOM patients withcholesteatoma were male (68%) than female (32%). Based on education level, the highest number of SMA was (52%).Based on occupation, people who do not work / school age suffer the most from CSOM with cholesteatoma (50%). Mostpatients present with the main complaint of watery and smelly ears (40%). It was found that the ossicular chain was erodedby 45 people (90%). Based on intraoperative findings at the location of cholesteatoma, it was found mostly in the tympaniccavity and mastoid as many as 35 people (70%). The most common intracranial complication was cerebral abscess in 27people (54%). The most common extracranial complications were retroauricular abscess in 24 people (48%). The mosterosion of the auditory bone chain was found and the location of most cholesteatoma formation was in the tympanic andmastoid cavity. Most intracranial complications are cerebral abscesses, while extracranial complications are retroauricularabscesses.